2020
DOI: 10.15282/mekatronika.v2i2.6750
|View full text |Cite
|
Sign up to set email alerts
|

Development of Consumers Management System via Face Classification

Abstract: To improve consumer experience and overall retail management, physical retailers may adapt consumer behaviour management systems using artificial intelligence to imitate the capability of consumer behaviour tracking in online shopping into physical retail. The proposed consumer behaviour management system consists of two parts - face recognition and consumer tracking at an area of interest. Both will be combined to produce a summary of individual customer’s visits to the shop. This information can be used to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…On the other hand, this study found that visitor management via mobile application usage has a significant positive impact on resident satisfaction (β 5 0.758, p-value 5 0.000). This study findings show that residents living at strata properties demand effective visitor Coding and questions Factor loading AVE Alpha Skew Kurt VM3: Visitors' arrival and departure data via application is effective and helps the property management provide better services (Oktaviandri and Foong, 2019;BK and Akshay, 2021; 0.893 À1.094 0.800…”
Section: Structural Modelmentioning
confidence: 86%
See 4 more Smart Citations
“…On the other hand, this study found that visitor management via mobile application usage has a significant positive impact on resident satisfaction (β 5 0.758, p-value 5 0.000). This study findings show that residents living at strata properties demand effective visitor Coding and questions Factor loading AVE Alpha Skew Kurt VM3: Visitors' arrival and departure data via application is effective and helps the property management provide better services (Oktaviandri and Foong, 2019;BK and Akshay, 2021; 0.893 À1.094 0.800…”
Section: Structural Modelmentioning
confidence: 86%
“…, 2019). According to Oktaviandri and Foong (2019), visitor management integration in mobile applications refers to a system that tracks the real-time activity of visitors in residential properties, enhancing monitoring capabilities. Without a property management application, visitors in high-rise condominium and strata properties must manually register themselves at the guard house and provide identification documents such as a driving licence.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations